The problem of studying the best educational experience - Tkach A.V (Kharkov National Pedagogical University, 2011)
In this paper the peculiarities of the views of scientists on the issues of determining the essence of good teaching experience, its dissemination and implementation in practice of education. The main stages of studying advanced pedagogical experience. It is shown the features of each stage. It is given the definition of best educational experience. Highlighted key terms that are used in the theory and practice work with the best educational experience.